The Emergence of Lying for Reputational Concerns in 5-Year-Olds - Klafka, Mareike; Liszkowski, Ulf (Frontiers in Psychology, 2021)
Research suggests that even young children engage in strategic behaviors to manipulate the impressions others form of them and that they manage their reputation in order to cooperate with others. The current study investigated whether young children also lie in order to manage their, or their group’s, reputation in front of ingroup and outgroup members. Five-year old children (n = 55) were randomly assigned to an individual reputation condition or a group reputation condition. Then, they played a mini dictator game in which they could share privately any number of their or their group’s stickers with an anonymous child. Participants then met ingroup and outgroup members, established through a minimal group design, via a pre-recorded, staged Skype call. Group members asked the participant how many stickers she, or her group, had donated. Results revealed that children stated to peers to have donated more than their actual donation, with no differences between conditions and no difference toward ingroup and outgroup members. Findings suggest that by 5 years of age, children use lying as a strategy to manage their reputation.